Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine the end behavior of the polynomial function [tex]\( f(x) = 2x^3 - 3x^2 + 5x - 1 \)[/tex], we need to analyze the term that has the highest power, which dominates the behavior of the polynomial as [tex]\( x \to +\infty \)[/tex] and [tex]\( x \to -\infty \)[/tex].
1. Identify the highest degree term:
The polynomial function provided is [tex]\( f(x) = 2x^3 - 3x^2 + 5x - 1 \)[/tex]. The highest degree term here is [tex]\( 2x^3 \)[/tex].
2. Analyze the behavior as [tex]\( x \to +\infty \)[/tex]:
When [tex]\( x \to +\infty \)[/tex], the [tex]\( x^3 \)[/tex] term will dominate the polynomial because it grows faster than the other terms. Since the coefficient of [tex]\( x^3 \)[/tex] is positive (i.e., [tex]\( 2 \)[/tex]), as [tex]\( x \to +\infty \)[/tex], the [tex]\( 2x^3 \)[/tex] term will also grow to [tex]\( +\infty \)[/tex]. Therefore, [tex]\( f(x) \to +\infty \)[/tex] as [tex]\( x \to +\infty \)[/tex].
3. Analyze the behavior as [tex]\( x \to -\infty \)[/tex]:
Similarly, when [tex]\( x \to -\infty \)[/tex], the [tex]\( x^3 \)[/tex] term still dominates the behavior of the polynomial. However, the key difference is that the term [tex]\( x^3 \)[/tex] will now take very large negative values because raising a negative number to an odd power results in a negative number. Since the coefficient of [tex]\( x^3 \)[/tex] is positive, as [tex]\( x \to -\infty \)[/tex], the [tex]\( 2x^3 \)[/tex] term will grow to [tex]\( -\infty \)[/tex]. Therefore, [tex]\( f(x) \to -\infty \)[/tex] as [tex]\( x \to -\infty \)[/tex].
Combining these observations, the end behavior of the polynomial function [tex]\( f(x) = 2x^3 - 3x^2 + 5x - 1 \)[/tex] is as follows:
- As [tex]\( x \to -\infty \)[/tex], [tex]\( f(x) \to -\infty \)[/tex].
- As [tex]\( x \to +\infty \)[/tex], [tex]\( f(x) \to +\infty \)[/tex].
In conclusion, the correct identification of the end behavior for the polynomial function is:
[tex]\[ \begin{array}{r} f(x) = 2x^3 - 3x^2 + 5x - 1 \\ f(x) \to -\infty \text{ as } x \to -\infty \\ f(x) \to +\infty \text{ as } x \to +\infty \end{array} \][/tex]
1. Identify the highest degree term:
The polynomial function provided is [tex]\( f(x) = 2x^3 - 3x^2 + 5x - 1 \)[/tex]. The highest degree term here is [tex]\( 2x^3 \)[/tex].
2. Analyze the behavior as [tex]\( x \to +\infty \)[/tex]:
When [tex]\( x \to +\infty \)[/tex], the [tex]\( x^3 \)[/tex] term will dominate the polynomial because it grows faster than the other terms. Since the coefficient of [tex]\( x^3 \)[/tex] is positive (i.e., [tex]\( 2 \)[/tex]), as [tex]\( x \to +\infty \)[/tex], the [tex]\( 2x^3 \)[/tex] term will also grow to [tex]\( +\infty \)[/tex]. Therefore, [tex]\( f(x) \to +\infty \)[/tex] as [tex]\( x \to +\infty \)[/tex].
3. Analyze the behavior as [tex]\( x \to -\infty \)[/tex]:
Similarly, when [tex]\( x \to -\infty \)[/tex], the [tex]\( x^3 \)[/tex] term still dominates the behavior of the polynomial. However, the key difference is that the term [tex]\( x^3 \)[/tex] will now take very large negative values because raising a negative number to an odd power results in a negative number. Since the coefficient of [tex]\( x^3 \)[/tex] is positive, as [tex]\( x \to -\infty \)[/tex], the [tex]\( 2x^3 \)[/tex] term will grow to [tex]\( -\infty \)[/tex]. Therefore, [tex]\( f(x) \to -\infty \)[/tex] as [tex]\( x \to -\infty \)[/tex].
Combining these observations, the end behavior of the polynomial function [tex]\( f(x) = 2x^3 - 3x^2 + 5x - 1 \)[/tex] is as follows:
- As [tex]\( x \to -\infty \)[/tex], [tex]\( f(x) \to -\infty \)[/tex].
- As [tex]\( x \to +\infty \)[/tex], [tex]\( f(x) \to +\infty \)[/tex].
In conclusion, the correct identification of the end behavior for the polynomial function is:
[tex]\[ \begin{array}{r} f(x) = 2x^3 - 3x^2 + 5x - 1 \\ f(x) \to -\infty \text{ as } x \to -\infty \\ f(x) \to +\infty \text{ as } x \to +\infty \end{array} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.